Postural control impairments following neurotoxic chemotherapy in women with cancer: a prospective observational study - Aline Reinmann; Alexandre Bodmer; Thibaud Koessler; Joseph Gligorov; Anne-Violette Bruyneel (BMC Women's Health)
Abstract Purpose This study aimed to compare changes in postural control in different testing conditions involving sensory disturbances, quality of life and neurotoxicity concerns in women with cancer before and after chemotherapy with taxanes. The second aim was to compare postural control between chemotherapy-induced peripheral neuropathy (CIPN) severity subgroups. Method The 33 participants with breast cancer (age 48.15 ± 9.88 years) were tested during the month preceding (baseline) and the month after the end of chemotherapy. Postural control was assessed on a force platform (100 Hz) in different conditions: eyes open/closed, rigid/foam surface, with/without tendon vibration, dual task, and limits of stability. CIPN severity and neurotoxicity concerns were also evaluated. Paired t-tests or Wilcoxon sign rank tests were used, and a Benjamini-Hochberg correction was applied. Results After chemotherapy, greater postural adjustments were required to maintain balance in the reference condition (p ≤ 0.02), and in conditions with visual (p ≤ 0.02), foam (p ≤ 0.04), and dual task disturbances (p ≤ 0.01), but not in the vibration and limits of stability conditions. No difference was found between the CIPN subgroups. The neurotoxicity score worsened after chemotherapy (-8.61 ± 7.53, p ≤ 0.01). Conclusions Postural control was impaired after chemotherapy, particularly in conditions with visual disturbances and dual task. Anteroposterior center of pressure displacements with mediolateral ground reaction forces were particularly increased. Clinical implications Systematic assessment of postural control with eyes closed in women with breast cancer would help to identify chemotherapy-induced postural control disorders and determine treatment needs. Trial registration Clinical Trial Registration number NCT04692168. Registration date: 28.12.2020